Community-based educational intervention improved the diversity of complementary diets in western Kenya: results from a randomized controlled trial - Waswa, Lydiah M.; Jordan, I.; Herrmann, J.; Krawinkel, M.B.; Keding, G.B. (Cambridge University Press, 2015)
Lack of diversity is a major factor contributing to inadequate nutrient intakes among children during the complementary feeding period in many rural areas in developing countries. This has been attributed to inadequate feeding practices and nutrition knowledge among their caregivers. The aim of the present study was to assess the effect of an educational intervention on children’s dietary diversity and nutrition knowledge of caregivers.Cluster randomization was applied and twenty matched village pairs were randomly assigned to the intervention or control group. The nutrition education intervention consisted of four sessions comprising of group trainings and cooking demonstrations that were conducted over a period of 5 months.Households in rural communities in Bondo and Teso South sub-counties, western Kenya.Caregivers with children aged 6–17 months receiving nutrition education.The children’s dietary diversity scores (CDDS) and nutrition knowledge scores of the caregivers improved significantly in the intervention group at endline. The treatment effect on CDDS was positive and significant (P=0·001). The CDDS rate of the children in the intervention group was 27 % larger than it would have been without the treatment effect. The intervention also had a significant effect on the caregivers’ nutrition knowledge scores (incidence rate ratio=2·05; P<0·001). However, the nutrition knowledge of the caregivers did not have a significant effect on CDDS (P=0·731).The nutrition education intervention led to improvements in children’s dietary diversity and nutrition knowledge of the caregivers.